PEMBELAJARAN KEBUDAYAAN PRANCIS MELALUI GOOGLE CLASSROOM - Siti Umaya; Lina Syawalina; Dian Agustina Pratama; Citra Kandiawan (Jurnal SORA, 2021)
The research entitled “Learning French Culture through Google Classroom” is a descriptive study that aims to provide an overview of the learning process using Google Classroom in the Civilisation Française course as an alternative learning media in learning French culture. In addition, this study provides an overview and information about the profile level of the mastery of the students’ cultural knowledge during the learning process in the course. To obtain the data, the researchers use several research techniques, namely direct observation, interview, questionnaire, literature review, and documentation of the population and samples, that is all chracteristics of the teaching and learning process using Google Classroom and all registered semester II students who take the course. The research team hopes that the results of this study can contribute to improving the quality of teaching, especially cultural teaching in the Civilisation Française course at the French Language Department of STBA Yapari-ABA Bandung and improving the French language competence and the mastery of students’ cultural knowledge.